Allergen immunotherapy on the way to product-based evaluation—a WAO statement - Bachert, Claus; Larché, Mark; Bonini, Sergio; Canonica, Giorgio Walter; Kündig, Thomas; Larenas-Linnemann, Desiree; Ledford, Dennis; Neffen, Hugo; Pawankar, Ruby; Passalacqua, Giovanni (The World Allergy Organization journal, 2015)
Allergen immunotherapy (AIT) is widely used in clinical practice for patients with moderate to severe allergic rhinitis due to inhalant allergens and may be delivered via subcutaneous (SCIT) and sublingual routes (SLIT). However, the quality of evidence for individual AIT products is very heterogeneous, and extensions of overall conclusions (“class effects”) on the efficacy and disease-modifying effects to all AIT products are unjustified. In contrast, each product needs to be evaluated individually, based on available study results, to justify efficacy and specific claims on sustained and disease modifying effects per allergen and targeted patient group (children vs. adults, allergic rhinitis vs. asthma). WAO intends to support the current development to evidence-based AIT, which ultimately will lead to a more efficacious treatment of allergic patients and the appropriate recognition of AIT.